Influence of post clad heat treatment on microstructure and slurry erosion characteristics of Ni-based microwave clad. (February 2021) - Singh, Bhupinder; Zafar, Sunny
Abstract: In this study, effect of high temperature heat treatment on microstructure and erosive wear performance of Ni-based clad was investigated. The clad was developed on a hydroturbine steel (CA6NM) substrate using microwave hybrid technique. The as-clad microstructure comprised of rod-like Cr enriched M7 C3 carbides in γ-(Ni, Fe) solid solution. Post clad heat treatment at 750 °C led to M7 C3 →M23 C6 transformation accompanied by increase in carbide volume fraction. On the other hand, heat treatment at 1000 °C clad resulted in partial dissolution of the eutectic carbides. Among the tested samples, 750 °C heat treated sample exhibited higher erosion resistance. The erosive wear behaviour of Ni-based clad, before and after heat treatment, showed good correlation with hardness (at 30°) and elastoplasticity (at 90°). Highlights: Influence of heat treatment on slurry erosion of Ni-based microwave clads. M7 C3 .→M23 C6 transformation at 750 °C, increased carbide volume fraction. Heat treatment at 750 °C increased high hardness and elastoplasticity. High hardness (at 30°) and elastoplasticity (at 90°) lowered erosion loss.